Student's Error Analysis In Solving Definite Integral Problem Based On Multiple Intelligences - Fatimah Ihza Aulia; Ika Kurniasari (Program Studi S1 Matematika UNESA, 2022)
One of the factors that students perform errors in solving mathematic problem is student’s intelligence. Gardner mentioned there are eight types of multiple intelligences, there are linguistic, logical mathematical, kinesthetic, musical, spatial, interpersonal, intrapersonal and naturalistic. Student’s error can be analyzed using Newman’s error analysis which contains five types of errors, there are reading error, comprehension error, transformation error, process skill error, and encoding error. This research is descriptive qualitative research which aims to describe the types of student’s error in solving definite integral based on multiple intelligences. The subjects of this research are three grade XII senior high school students in Sidoarjo whom have intelligences related to mathematic, there are logical mathematical intelligence, linguistic intelligence and spatial intelligence. Data was collected by giving multiple intelligences test, definite integral problems and interview. Data analysis technique are data reduction, data presentation and data verification. The result of this research showed that: (1) students with logical mathematical intelligence perform transformation error, process skill error and kesalahan encoding error; (2) students with linguistic intelligence perform reading error, comprehension error, transformation error, process skill error and encoding error; (3) students with spatial intelligence perform reading error, transformation error and encoding error.